2011
DOI: 10.1007/s00414-010-0541-6
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Greulich and Pyle method for age assessment in forensic practice on an Italian sample

Abstract: Our study shows that although the GPM is a reproducible and repeatable method, there is a wide margin of error in the estimation of chronological age, mainly in the critical estimated ages of 14 and 18 years old in both males and females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(38 citation statements)
references
References 24 publications
3
28
0
7
Order By: Relevance
“…Radiologists are commonly asked to determine the age of an individual for legal or medical purposes. The most common method used for age determination in our center is the evaluation of hand wrist x-rays by Greulich and Pyle method (18). The recent increase of asylums and illegal immigration further emphasized the importance of forensic determination of the age.…”
Section: Discussionmentioning
confidence: 99%
“…Radiologists are commonly asked to determine the age of an individual for legal or medical purposes. The most common method used for age determination in our center is the evaluation of hand wrist x-rays by Greulich and Pyle method (18). The recent increase of asylums and illegal immigration further emphasized the importance of forensic determination of the age.…”
Section: Discussionmentioning
confidence: 99%
“…This method does not factor the influence of nutrition, ancestry, and environmental and socio-economic status in the age estimations performed, consequently resulting in inaccurate age estimations. Tise et al[33] analysed the reproducibility and accuracy of this method in an Italian sample to ascertain the applicability of the atlas approach at the critical age thresholds of 14 and 18 years.The results indicated a wide margin of error in the estimation of chronological age for the age thresholds of 14 and 18 years in both the sexes. The Greulich-Pyle atlas was not designed for the purpose of age estimations and involves significant amount of subjectivity in the interpretation of the hand-wrist x-rays[34].…”
mentioning
confidence: 99%
“…Tisè M. et al [15] also studied the applicability of the GPM for age assessment on an Italian sample. Their results showed that, although the GPM is a reproducible and repeatable method, there is a wide margin of error in the estimation of chronological age and great variability of error in the critical estimated ages of 14 and 18-year-olds in both males and females.…”
Section: Discussionmentioning
confidence: 97%